Psychological impact of COVID-19 on medical interns - Findings from a nationwide survey - Chandrashekar B Huded; Smitha Lamiya Rasquinha; Pradyumna Rao (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The COVID-19 pandemic has negatively impacted the mental health of health-care workers worldwide. This study aimed to estimate the prevalence of psychological distress in medical interns during the pandemic and examine the factors influencing it. MATERIALS AND METHODS: A cross-sectional online survey was conducted using snowball sampling among 764 medical interns across India, who were evaluated using the Kessler Psychological Distress Scale, Fear of COVID-19 Scale, and semi-structured questionnaires. Univariate analysis was done using Chi-square test, unpaired t-test, and ANOVA, while multivariate analysis was conducted using binary logistic regression. RESULTS: 57.5% of the interns reported psychological distress, with 39.8% having moderate-to-severe distress. Past consultation with a mental health professional (odds ratio [OR]: 2.15; 95% confidence interval [CI]: 1.42-3.26) and perceived lack of support from friends (OR: 2.33; 95% CI: 1.33-3.99) and faculty (OR: 2.15; 95% CI: 1.41-3.28) were the most significant predictors of distress. Fear of COVID-19 was higher in interns who were female, were medically ill, were dissatisfied with the pandemic preparedness at the hospital, and perceived the faculty to be less approachable and supportive. Majority of the interns felt that the pandemic had hampered their learning and were worried about an extension to their internship and their performance in the postgraduate entrance examinations. CONCLUSIONS: Psychological distress was highly prevalent among interns, with several workplaces and personal factors affecting the distress levels. Most interns perceived a negative impact of the pandemic on their learning and career. Addressing these issues could help alleviate the distress and bolster the mental health of interns.